2018
DOI: 10.1186/s12891-018-2289-y
|View full text |Cite
|
Sign up to set email alerts
|

Hip stability after total hip arthroplasty predicted by intraoperative stability test and range of motion: a cross-sectional study

Abstract: BackgroundDislocation continues to be a common complication following total hip arthroplasty (THA). A larger intraoperative range of motion (ROM) is believed to minimize dislocation risk, and intraoperative stability tests have been used to assess the ROM. However, it is not clear whether or not intraoperative stability tests can predict hip stability after THA. It is also unclear which angles are required in intraoperative stability tests. We investigated the usefulness of intraoperative stability tests, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 26 publications
(42 reference statements)
0
22
0
Order By: Relevance
“…The majority of the proponents of the posterior approach carry out dynamic testing for hip stability and soft tissue tension across the hip (i.e., push-pull test). Tanino et al , from the study of 185 hips, noted that with a 32 mm metal femoral head, that an intraoperative stability test, particularly the IR angle, was a useful method to predict hip stability following THA (41). If a trochanteric osteotomy is performed, the risk of dislocation is increased, particularly if a nonunion develops (24).…”
Section: Incidence Of Dislocation Following Total Hip Arthroplasty (Tmentioning
confidence: 99%
“…The majority of the proponents of the posterior approach carry out dynamic testing for hip stability and soft tissue tension across the hip (i.e., push-pull test). Tanino et al , from the study of 185 hips, noted that with a 32 mm metal femoral head, that an intraoperative stability test, particularly the IR angle, was a useful method to predict hip stability following THA (41). If a trochanteric osteotomy is performed, the risk of dislocation is increased, particularly if a nonunion develops (24).…”
Section: Incidence Of Dislocation Following Total Hip Arthroplasty (Tmentioning
confidence: 99%
“…As the present study included many cases of developmental dysplasia of the hip, in which the degree of femoral anteversion was significantly large, we employed larger target angles [28]. Recently, the concept of the IR angle was reported to be a useful method for predicting hip stability after THA, and an IR angle of 51°was suggested to be an appropriate cut-off point for such predictions [21]. Because a recent study reported that stem anteversion had the strongest effect on the IR angle [29], we fine-tuned stem anteversion prior to the final implantation to achieve an appropriate IR angle.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that the intraoperative stability test, especially measuring the IR angle (the range of internal rotation under 90°hip flexion and 0°a bduction/adduction), is a useful method for predicting hip stability after THA. An IR angle of 51°was set as the cut-off point for such predictions [21]. After removing the acetabular osteophytes and femoral neck remnants, the target angle was decided by fine-tuning the femoral broach and neck length to acquire an IR angle of > 51°w ithout causing anterior instability.…”
Section: Surgical Technique and Measurementsmentioning
confidence: 99%
“…As the present study included many cases of developmental dysplasia of the hip, in which the degree of femoral anteversion was significantly large, we employed larger target angles [28]. Recently, the concept of the IR angle was reported to be a useful method for predicting hip stability after THA, and an IR angle of 51° was suggested to be an appropriate cut-off point for such predictions [21]. A recent study reported that stem anteversion had the strongest effect on the IR angle [29].…”
Section: Discussionmentioning
confidence: 99%